Supermassive black holes - King, Andrew R. 1947- (Cambridge University Press, 2023)
This is a coherent and accessible account of the concepts that are vital for understanding supermassive black holes. The treatment is largely analytic and gives in-depth discussions of the underlying physics. It will be useful for advanced courses in astrophysics, and as a handbook for active researchers